An account of second language teaching and learning in a multi-standard farm school classroom, utilising an ethnographic approach - Krause, Siobbhan Karen (Rhodes University, Faculty of Education, Department of Education, 1998)
Multi-standard classrooms are a distinctive feature of many South African farm schools. This study adopts an ethnographic approach in order to explore how classroom life in one particular Eastern Cape multistandard farm school classroom is shaped by a set of circumstances which influence the nature of teaching and learning in that classroom. The research focuses on the extent to which the difficulties associated with teaching a multi-standard class dictate the teacher's approach to lesson planning and style of teaching and how the resultant pattern of interaction influences language learning within a second language context. Data from a variety of sources, obtained primarily through classroom observations, interviews and questionnaires, is presented. Findings tend to indicate that the demands made on the teachers and pupils in terms of large, multi-standard classes, second language medium of instruction and lack of teaching aids, encourages the use of rote learning techniques which are not conducive to language learning. The pattern of interaction that predominates is a teacher-led series of questions and prompts followed by a chorus response from the pupils. This pattern tends to undermine the communicative aspects of language learning by reducing natural interaction and results in pupil passivity as language learners.
Keywords: English language -- Study and teaching -- South Africa -- Foreign speakers; Rural schools -- South Africa; Community and school -- South Africa; English language -- Study and teaching -- Foreign speakers; Education, Rural -- South Africa; Black people -- Education -- South Africa